2022
DOI: 10.1016/j.isci.2022.103780
|View full text |Cite
|
Sign up to set email alerts
|

Development of human alveolar epithelial cell models to study distal lung biology and disease

Abstract: Many acute and chronic diseases affect the distal lung alveoli. Alveolar epithelial cell (AEC) lines are needed to better model these diseases. We used de-identified human remnant transplant lungs to develop a method to establish AEC lines. The lines grow well in 2-dimensional (2D) culture as epithelial monolayers expressing lung progenitor markers. In 3-dimensional (3D) culture with fibroblasts, Matrigel, and specific media conditions, the cells form alveolar-like organoids expressing mature AEC markers inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 112 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…For example, researchers have found that aquaporin 5 ( AQP5) is more highly expressed in human lung organoids than lung tissues in the datasets ‘Odd000570’, ‘Odd000657’ and ‘Odd001044’ through the organoid comparison module ( Supplementary Figure S1A ). It has been reported that AQP5 is highly expressed in lung organoids as a marker of alveolar epithelial cells ( 37 ). In addition, users can also apply the organoid development module to find that the expression levels of some homeobox (Hox) genes and LIM homeobox 1 ( LHX1) are highly correlated with the developmental time of kidney organoids in the dataset ‘Odd001105’ ( Supplementary Figure S1B ) ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers have found that aquaporin 5 ( AQP5) is more highly expressed in human lung organoids than lung tissues in the datasets ‘Odd000570’, ‘Odd000657’ and ‘Odd001044’ through the organoid comparison module ( Supplementary Figure S1A ). It has been reported that AQP5 is highly expressed in lung organoids as a marker of alveolar epithelial cells ( 37 ). In addition, users can also apply the organoid development module to find that the expression levels of some homeobox (Hox) genes and LIM homeobox 1 ( LHX1) are highly correlated with the developmental time of kidney organoids in the dataset ‘Odd001105’ ( Supplementary Figure S1B ) ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…[40] Other models were either not cultured under ALI conditions or demonstrated the formation of inhomogeneous cellular multilayers when seeded on Transwell inserts. [38,77] What all of the afore-mentioned studies have in common, is that they either did not assess barrier integrity at all or reported TEER values <300 Ω cm 2 and/or have not been characterized in terms of drug transport. In a model reported by He et al, human IPSCs were differentiated to alveolar organoids and in parallel to endothelial cells before both cell types were seeded on artificial or reconstituted basement membranes under ALI-conditions.…”
Section: Figurementioning
confidence: 99%
“…[34] A further aggravating factor is that such models are experimentally challenging to establish, costly to implement and might hamper inter-laboratory comparison due to complex differentiation protocols. [77,78] One alveolar epithelial model which is based on differentiated human IPSCs grown on 96-well Transwell inserts under ALI conditions, reported tight barrier properties indicated by TEER values > 1000 Ω cm 2 and would thus be suitable for drug transport studies. [79] These TEER values, however, were measured using a custom-built device and were only compared to literature derived TEER values from hAEpCs.…”
Section: Figurementioning
confidence: 99%
“…In addition, Tran and colleagues created a human AEC2 immortalized cell line using SV40 large T antigen lentiviral transfection and Y-27632 (a RHO/ROCK pathway inhibitor) media supplementation. After initial 2-dimensional expansion, AEC2s cocultured with a mouse lung fibroblast cell line formed alveolospheres expressing AEC1 and AEC2 markers ( 50 ).…”
Section: Optimization Of Culture Media Components and Cell Compositionmentioning
confidence: 99%